Pengaruh Intellectual Capital, Kinerja Keuangan, Sales Growth, dan Arus Kas Operasi terhadap Financial Distress pada Perusahaan Sektor Property & Real Estate yang Terdaftar di BEI Periode 2020-2023 - Andini, Aulia Putri; Ananto, Rangga Putra; Eliyanora, Eliyanora (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to identify factors that contribute to financial distress in property and real estate companies listed on the IDX between 2020 and 2023 in terms of intellectual capital, sales growth, operational cash flow, profitability, solvency, and liquidity ratios. The financial distress of each company was assessed using the modified Altman Z-Score approach. An approach known as purposive sampling was used in the sampling process. With a total of 87 data observations, this study came from a population of 93 companies, with 28 companies being sampled. Multiple linear regression analysis was the approach used in this study. The study found that financial distress is affected by intellectual capital, liquidity ratio, and solvency ratio, but not by profitability ratio, sales growth, or operating cash flow.